OVERVIEW OF AUTONOMOUS WEARABLE SYSTEM FOR VITAL SIGNS MEASUREMENT WITH ENERGY-HARVESTING MODULE - ARUNA NAMDEO CHAUDHARI; PROF. SHRINIVAS ZANWAR; DR. U. B. SHINDE (International Journal of Innovations in Engineering Research and Technology, 2021)
Wearable devices have become very popular now days across the youth over the world. These devices have become the part of our day to day life. The market of wearable devices has grown in India in last 5 years. These mainly include the smart watches, headsets and other virtual reality devices. With development of internet of things (IoT) technology it has become possible to design and develop the smart wearable devices. The problem associated with such devices is the battery capacity and capacity to weight ratio. To overcome this problem, energy harvesting becomes and important. Authors have presented the overview of various wearable technologies and harvesting module of energy for such devices in this paper.